Toxicity evaluation of Cosmos caudatus, Periskia bleo and Averrhoa bilimbi on sprague dawley rats / Farah Amna Othman - Othman, Farah Amna (2015)
Cosmos caudatus, Periskia bleo and Averrhoa bilimbi are among the common plants regularly consumed and used for the treatment of various ailments in Malaysia. The present study evaluated the acute and subacute toxicity of C. caudatus, P. bleo and A. bilimbi in vivo, which followed closely the Organization for Economic Co-operation and Development (OECD) Guidelines 423 and 407, respectively. Acute toxicity was tested on 3 groups, each with 6 female rats, at the doses of 2000 and 5000 mg/kg b.wt., respectively of each extract. Meanwhile, subacute. toxicity tests involved 4 groups of rats, with 6 males and 6 females for each group. The doses used were 125, 250 and 500 mg/kg b.wt. of the extracts. The control groups in both toxicity studies received saline. The values of Lethal Dose (LDso), haematological, biochemical as well as histopathological assessments were evaluated. Acute toxicity study revealed female rats could tolerate 5000 mg/kg b.wt. of C. caudatus, P.bleo and A. bilimbi ethanolic extracts. Neither mortality nor treatment related changes in their behaviour and external appearance were observed, which indicated that the LDso of all the extracts were higher than the tested dosage. However, consideration should be taken with 5000 mg/kg b.wt. dose of P. bleo, since sign of dizziness was detected among experimental rats. Subacute toxicity study of C. caudatus showed that the extract caused slight decreased in red blood cell count (RBC) and packed cell volume (PCV) in all treated male rats, PCV value of 250 mg/kg b.wt of female rats, white blood cell count (WBC) of both 125 and 500 mg/kg b.wt. of male rats and in haemoglobin (Hb) level of 125 mg/kg b.wt. of both male and female treated rats. Slight increased in the value of mean corpuscular haemoglobin (MCH) was observed in groups of 250 and 500 mg/kg b.wt. of male rats. Similarly, mean corpuscular haemoglobin concentration (MCHC) also increased in all treated rats. In subacute toxicity study of P. bleo, slight decreased in the PCV values of 250 mg/kg b.wt. of female rats, MCH value of 125 mg/kg b.wt. of male rats and in MCHC value of 125 mg/kg b.wt. of female rats, along with an increased in the MCHC value of 250 mg/kg b.wt. of female rats. In addition, A. bilimbi showed a decreased in PCV value of 250 mg/kg b.wt. of male rats, and an increased in the MCHC value of250 mg/kg b.wt. of male rats and in Hb value of 500 mg/kg b.wt. of female rats. Even though statistical differences were obtained among dosages, all values obtained were within the standard laboratory range. Histological assessment revealed normal cellular architectures in all selected organs among the treated rats. This study also revealed that the extract of C. caudatus and P. bleo both possessed hepatoprotective effects, which lowered the ALT levels in 5000 mg/kg b.wt. for C. caudatus extract, in 2000 mg/kg b.wt. and in all treated female rats of 125, 250 and 500 mg/kg b.wt. for P. bleo extract. AST levels of 500 mg/kg b.wt. of male rats for C. caudatus extract was also reduced. Increased RBC at higher dosages of 2000 mg/kg b.wt. for C. caudatus and P. bleo, and in 5000 mg/kg b.wt. of A. bilimbi, even though not significant, indicated that all of these extracts could possessed haematopoietic potential. The findings therefore, revealed that the ethanolic extract of C. caudatus, P. bleo and A. bilimbi were evaluated to be non toxic to the tested animals, hence, it is postulated that the extracts are safe for human consumption and to be used for further potential drug development.